ANALISIS KEAKURATAN FORECAST RESIN ABS GRADE 500 322 MENGGUNAKAN PENDEKATAN MEAN ABSOLUTE PERCENTAGE ERROR (MAPE): STUDI KASUS INDUSTRI MANUFAKTUR PLASTIC COLORING DAN COMPOUNDING - Dwi Irwati; Ade Nurul Hidayat (Industry Xplore, 2023)
The plastic resin coloring industry has a very important role in the molder supply chain. Materials must be imported from abroad with a long enough lead time, so material purchases are made based on the forecast provided by the molder. The constraints that occur are forecast inaccuracies which result in an increase in inventory level of material and a potential shortage of material at the customer. This research is a descriptive research with a quantitative approach, where the research method is carried out by interviews and literature studies. This research is aimed at measuring the extent to which forecast accuracy is carried out by molders using the MAPE (Mean Absolute Percentage Error) method, the results of the study show whether or not a forecast is feasible. The results of this study show an average MAPE of 36.5% so that it can be categorized as feasible. Even though the forecast is categorized as feasible, PT X must respond properly to this forecasting inaccuracy so that the supply to the molder is not disrupted. In this study, PT X had to make adjustments to the material arrival planaccording to the current month's material needs. On the other hand, it is no less important to carry out active communication and provide education to molders about the importance of forecast accuracy, so that it can provide benefits for the company itself and the molder.Keywords: Forecasting; MAPE; Molder